Reinach and Kantorowicz: Justice, Phenomenological Realism and the Free Law Movement - Baltzer-Jaray, Kimberly (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
Adolf Reinach met and befriended Hermann Kantorowicz in one of Lujo Brentano’s political economy seminars during the 1901/1902 academic year at the University of Munich. After Munich, Kantorowicz would go on to be a major contributor to the Free Law Movement (Freirechtsbewegung) in Germany and play an important role in the development of the sociology of law in the 20th century. Reinach encountered the work of Edmund Husserl while studying with Lipps and later became central to the phenomenological movement in Göttingen. But all the while he remained interested in and focused on issues related to justice. His last scholarly publication before leaving for battle in WWI, Die apriorischen Grundlagen des bürgerlichen Rechtes (The a priori Foundations of Civil Law, 1913) published in the very first edition of the Jahrbuch für Philosophie und phänomenologische Forschung (Yearbook for Philosophy and Phenomenological Research) is a testament to this. Here we see Reinach taking his phenomenological education and applying it to entities of justice. I believe Kantorowicz inspired this lasting interest in matters of justice. This essay will focus on the influence of Kantorowicz on Reinach, and while doing so attempt to flesh out and contrast the ways in which these two men sought to overcome the problems of justice (Recht) of their time. Many of these problems still continue to be relevant today.